Startup Ecosystems Components for an Interpretative Model and International Benchmarks - Greco, Fabio (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book analyzes the components of the startup ecosystem, including the characteristics that can favor or disadvantage the development of new innovative ventures. The author believes it is essential to identify crucial variables of start-up ecosystems that have a context-specific influence on the well-being and development of startups. In this regard, the book analyzes the concept of the start-up ecosystem both from the point of view of scholars and professionals. The author then deals with the diverse approaches to studying startup ecosystems, which have over the years become increasingly complex, and less linear, making systematization indispensable. The author provides therefore a classification with a transversal logic with respect to this diversity of contributions in the literature. The main theoretical contributions to start-up ecosystems are grouped according to the attention they place on three different variables: territorial contexts, resources, and actors. The author also presents qualitative, interview-based, research using narrative analysis mode to understand the three variables. The work provides, on the one hand, the proposal of a framework as a theoretical interpretative model useful both for the description of the fundamental components of the start-up ecosystem, and also useful for giving a boost to future research. On the other hand, the book also presents evidence of a practical nature useful to support and guide the choices of startup founders and of managers of companies and institutions that orbit within start-up ecosystems.
Part I The components of the start-up ecosystem -- Introduction -- Chapter 1: A Research Design on Start-up Ecosystems -- Chapter 2: Studies on entrepreneurship and the phenomenon of start-ups -- Chapter 3: The support mechanisms for innovative entrepreneurship: Start-up accelerators and incubators -- Chapter 4: Start-up ecosystems and institutions: The role of universities and academic entrepreneurship -- Chapter 5: Access to new technologies as a lever for start-up scalability -- Part II Benchmarking for start-up ecosystems -- Chapter 6: International Benchmark for Italian Start-up Ecosystems.
Keywords: New business enterprises; Venture capital; Technological innovations; Start-Ups and Venture Capital; Economics of Innovation; Innovation and Technology Management